Comprehensively Deepen the Reform of Agricultural Land in Anhui Province by Innovating and Inheriting the Red Culture of Xiaogang - Yan, Wenhao (International Journal of Social Sciences and Public Administration, 2024)
Red culture is a culture created under the leadership of the proletariat and guided by Marxist theory. In the process of rural reform in China, Xiaogang Village in Fengyang, Anhui Province has given birth to a red culture represented by the red spirit of Xiaogang. On the basis of clarifying the connotation of red culture and exploring the emergence and development of the Xiaogang spirit, this study investigates the innovative reform of the agricultural land system in Xiaogang Village, and summarizes three reform directions: continuously deepening the rural land system reform, actively exploring rural economic reform, and innovating and strengthening rural grassroots governance reform. Based on the current rural land system in Anhui Province, where the ownership of rural collective property rights is unclear, the granting of agricultural land property rights is insufficient, and the protection of farmers’ land rights is incomplete, this paper proposes a path to comprehensively deepen the reform of agricultural land in Anhui Province by clarifying rural collective property rights, granting agricultural land property rights, and improving the protection of farmers’ rights and interests.